KLAUSUL BAKU PRASYARAT JUAL BELI MAKANAN DITINJAU DARI HUKUM BISNIS ISLAM (Jurnal Magister Hukum Perspektif, 2023)
The purpose of this study is to determine the existence of standard clauses in terms of Islamic business law. The type of research is juridical-empirical which is descriptive-qualitative with primary and secondary data sources. Data collection techniques are obtained through interviews, observation and documentation. The result of the research is that the inclusion of standard clauses comes from the concept of khiyar. This is in accordance with its structural principles. Thus, the sale and purchase transactions that occur between business actors and consumers do not harm each other. Warung Makan Geprek Jombang does not apply standard clauses in Islamic business law because in practice Warung Makan Geprek Jombang does not fulfill the existing standard clauses. The sale and purchase of Warung Makan Geprek Jombang has fulfilled the pillars and conditions set by the Jumhur Ulama. So this sale and purchase is valid when viewed from the pillars and conditions of buying and selling. The validity of buying and selling is not only viewed from the pillars and conditions, but must be seen from various aspects. In Islam, a sale and purchase like this is classified as a conditional sale and purchase. Keywords: Application of Standard Clauses, Sale and Purchase, Business Law